Clinical, neuropathological and molecular features of fatal human pegivirus-associated encephalitis. (September 2019) - Schmitt, LM; Balcom, E; Doan, M; Branton, WG; Jovel, J; Blevins, G; Edguer, B; Hobman, TC; Yacyshyn, E; Emery, D; Box, A; Power, C; et al.
Abstract : Flaviviruses include many viruses causing encephalitis, including West Nile encephalitis, St. Louis encephalitis, tick-borne encephalitis and Japanese encephalitis. Human pegivirus genotype-1 (HPgV-1) is a lesser known member of the Flaviviridae family and has been identified in human serum, cerebrospinal fluid and brain tissue. Here, we describe two adult patients with fatal HPgV-1-associated encephalitis. Neuroimaging revealed multifocal lesions, initially present in the periventricular and brain stem white matter, then one year later throughout the corona radiata bilaterally with marked involvement of the brainstem and cervical spinal cord. Phylogenetic analyses of HPgV-1 showed clustering of brain-derived sequences from both patients with other human pegiviruses. In both patients, a novel 87-nucleotide deletion in the viral NS2 gene was detected. The presence of positive and negative strand HPgV-1 RNA and viral antigens in both patients indicated viral persistence and replication in the CNS. Autopsy showed lymphocyte infiltration and gliosis predominantly in white matter of the brain and brain stem but, to a lesser extent, also in grey matter. Immunofluorescence revealed HPgV-1 NS5A antigen in lymphocytes as well as in astrocytes and oligodendrocytes. Thus, we hypothesize that the novel deletion in the NS2 coding region may have caused HPgV-1 neuroadaptation or might represent a yet unrecognized genotype of human pegivirus. LEARNING OBJECTIVES: This presentation will enable the learner to: 1. Describe the clinical and neuropathological features of fatal human pegivirus-associated encephalitis 2. Recognize the importance of molecular analysis in encephalitis cases with unknown etiology